Introduzindo o ensino da astronomia através da astronomia observacional - Raffa, Rodrigo Felipe (Universidade Federal de São Carlos, 2020)
Heavenly bodies can be observed everywhere in the night sky. With the naked eye we can identify around 6000 stars spread across 88 constellations. Faced with this countless number of stars, astronomy offers us the opportunity to explore the foundations of science and mathematics better than any other area of knowledge. Visualization plays a very important role in the teaching of science and mathematics. In this sense, Observational Astronomy can offer a wide range of options for the introduction and discussion of various subjects. In addition to the indisputable motivational characteristic for teaching science, astronomy updates and immerses us in an atmosphere of incredible scientific achievements and technological evolution. In view of this motivating and effervescent scenario of knowledge, we describe in this work an alternative to introduce the teaching of astronomy through observational astronomy, having the night sky as a laboratory and our eyes as the first measuring instrument to start the long journey of unraveling the mysteries of the universe. In this sense, everyone, from elementary school or undergraduate students, who have a more intimate contact with academic life, to the general public, has conditions and the potential to explore science and mathematics at the level they find most convenient, just by going deeper into his studies on observation techniques, technologies and instrumentation and why the universe behaves the way we see it. Here we explore the first steps to historically discuss the evolution of cultures of ancient people through theories and observations of the night sky with the naked eye. We also briefly address the most used coordinate systems to assist observers to locate themselves on our planet and the stars in the sky, the most well-known catalogs of celestial bodies, some of the phenomena and objects observed with the naked eye and the evolution of observational instruments. Furthermore, we present results obtained from naked eyes observations, recorded by an DSLR camera on an altazimuth tripod and how to treat the images in the open source software Astrometry to identify the stars and constellations in the region of the observed celestial sphere. We hope that this work can be useful to introduce astronomy in science-based courses such as Physics, Chemistry, Biology and Engineering, to help students in the process of scientific literacy for areas of advanced research as well as in the fundamental role that science has in society.
Introducing astronomy teaching through observational astronomy
Keywords: Astronomia observacional; Observações a olhos nus; Astrofotografia; Software Astrometry; Propriedades dos telescópios; Observational astronomy; Naked eye observation; Astrophotography; Telescope properties; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO